Gestão da satisfação e fidelidade do cliente :um estudo dos fatores que influenciam a satisfação e a fidelidade no turismo regional - Ferreira, Almir Miranda (2006)
This Thesis presents a contribution to the study of models of customer satisfaction, analyzing the relationship between construct satisfaction and its antecedents and consequences, carrying through a survey with tourists who live in states of northeast region, had used to travel by bus or their own car and used hotel of Natal in the period from march to june at 2004. The theory research is focused in concepts of customer satisfaction and loyalty, quality management system models and customer satisfaction measurement index models. For the field survey was applied a model with questions based on the norwegian customer satisfaction barometer - NCSB considered for Johnson et al., 2001 with 92 tourists. The results gotten for the multiple regression evidence that tourist satisfaction with respect to the hotel suffer fort influences of six drivers of quality and complaints management. However the factors that influencing tourist loyalty with hotel are affective commitment, satisfaction with the hotel and the complaints management